Current Knowledge on Polyethylene Terephthalate Degradation by Genetically Modified Microorganisms - Urbanek, Aneta K.; Kosiorowska, Katarzyna E.; Mirończuk, Aleksandra M. (Frontiers in Bioengineering and Biotechnology, 2021)
The global production of polyethylene terephthalate (PET) is estimated to reach 87.16 million metric tons by 2022. After single use, a remarkable part of PET is accumulated in the natural environment as plastic waste. Due to high hydrophobicity and high molecular weight, PET is hardly biodegraded by wild-type microorganisms. To solve the global problem of uncontrolled pollution by PET, degradation of plastic by genetically modified microorganisms has become a promising alternative for the plastic circular economy. In recent years many studies have been conducted to improve the microbial capacity for PET degradation. In this review, we summarize the current knowledge about metabolic engineering of microorganisms and protein engineering for increased biodegradation of PET